Pelatihan Pembuatan Ecoprint Untuk Menumbuhkan Kreativitas Dan Pendapatan Bagi Ibu-Ibu Pkk Di Kelurahan Lubang Buaya - Farida, Farida; Kurnia, Kurnia; Patriandari, Patriandari; Rosmawar, Cut; Marliana, Lina; Sandika, Tiara (Gapenas Publisher, 2022)
Ecoprint is a handicraft that supports the creation of superior products that can provide beauty and income for housewives. The aim of this Community Service activity at the Faculty of Economics and Business, As-Syafi'iyah Islamic University is to improve the economic level as a creative economic development by providing ecoprint training on household appliances for residents in Lubang Buaya Village. The object of this PKM is PKK women in Lubang Buaya Village so that they can improve the standard of living of the community through developing the creative economy. Ecoprinting training has an important role in increasing community creativity and the selling value of goods. In this training, the community outreach team will provide an explanation of the importance of ecoprinting training in the context of growing the creativity of PKK women and increasing the selling value of products. The selling value of an item is greatly influenced by factors such as unique design, product quality, and conformity with market trends. Therefore, ecoprinting training becomes relevant as a means of increasing creativity and income for PKK women in Lubang Buaya subdistrict.